Defining Iran : politics of resistance - Holliday, Shabnam J. (Ashgate, 2011)
Defining Iran presents a new and revealing analysis of the way in which Iranian political discourses compete with each other. Deconstructing the intellectual roots and development of Iranian nationalism through the twentieth century, Shabnam Holliday demonstrates how Iran's heritage and historical experience have influenced the construction and reconstruction of Iranian national identity.